Analisis Faktor-Faktor yang Mempengaruhi Motivasi Belajar Peserta Didik pada Pelajaran IPAS di Kelas 5 SD Negeri 10 Bakam - Rahma Wahyuni Baiti; M Iqbal Arrosyad; Vika Martahayu (CENDEKIAWAN, 2026)
This research aims to analyze the factors influencing students’ learning motivation in Natural and Social Sciences (IPAS) among fifth-grade students at SD Negeri 10 Bakam. Learning motivation is a key factor in determining the success of the learning process and is influenced by various internal and external factors. This study employed a qualitative approach using a case study design. Data were collected through in-depth interviews with teachers and parents, direct observation of learning activities, and questionnaires administered to students. The findings revealed that students’ learning motivation was influenced by several factors. First, students’ interest in IPAS learning materials could be enhanced through relevant and contextual learning approaches. Second, parental support played a significant role in creating a conducive learning environment at home. Third, the teacher’s role, including providing positive feedback, implementing varied learning methods, and fostering positive relationships with students, contributed to the development of students’ intrinsic motivation. The study concludes that improving students’ learning motivation in IPAS requires the use of diverse instructional methods, active parental involvement, and a supportive learning environment. Future research is recommended to further explore the implementation of technology-based learning strategies to enhance students’ learning motivation